Legacies of the Rue Morgue : Science, Space, and Crime Fiction in France - Goulet, Andrea (Book collections on Project MUSE., 2016)
Taking Edgar Allan Poe's 1841 "The Murders in the Rue Morgue" as an inaugural frame, Andrea Goulet traces shifting representations of violence, space, and nation in French crime fiction from serial novels of the 1860s to cyberpunk fictions today. She argues that the history of spatial sciences--geology, paleontology, cartography--helps elucidate the genre's fundamental tensions: between brutal murder and pure reason; historical past and reconstructive present; national identity and global networks. As the sciences underlying her analysis make extensive use of strata and grids, Goulet employs vertical and horizontal axes to orient and inform her close readings of crime novels. Vertically, crimes that take place underground subvert above-ground modernization, and national traumas of the past haunt present criminal spaces. Horizontally, abstract crime scene maps grapple with the sociological realities of crime, while postmodern networks of international data trafficking extend colonial anxieties of the French nation. Crime gangs in the catacombs of 1860s Paris. Dirt-digging detectives in coastal caves at the fin-de-siecle. Schizoid cartographers in global cyberspace. Crime fiction's sites of investigation have always exposed central rifts in France's national identity while signaling broader, enduring unease with violent disruptions to social order. Reading murder novels of the last 150 years in the context of shifting sciences, Legacies of the Rue Morgue provides a new spatial history of modern crime fiction.